Family stress during the pandemic worsens the effect of adverse parenting on adolescent sleep quality. (January 2022) - Zhang, Linhao; Cui, Zehua; Sasser, Jeri; Carvalho, Cory; Oshri, Assaf
Abstract: Background: Adverse parenting is consistently associated with increased sleep problems among adolescents. Shelter-in-Place restrictions and the uncertainty linked to the Covid-19 pandemic have introduced new stressors on parents and families, adding to the risk for youth's sleep problems. Objective: Using multidimensional assessments of child maltreatment (CM; threat vs. deprivation), the present study examined whether parent-report and child-report of Covid-19 related stress potentiated the effect of CM on sleep problems among boys and girls. Participants and setting: The study focused on a sample of 124 dyads of adolescents ( M age  = 12.89, SD  = 0.79; 52% female) and their primary caregivers (93% mothers) assessed before and during the pandemic (May to October 2020). Method: Data were obtained from both youth and their parents. Structural equation modeling (SEM) was used to test all study hypotheses. Simple slopes and Johnson-Neyman plots were generated to probe significant interaction effects. Results: Deprivation, but not threat, directly predicted increased sleep problems among boys during the pandemic. Additionally, elevation in Covid-19 stress (both parent and child report) intensified the link between CM (threat and deprivation) and sleep problems among boys. Conclusion: Our findings inform prevention and intervention efforts that aim to reduce sleep problems among boys during stressful contexts, such as the Covid-19 pandemic.